Uji Efikasi Bioinsektisida Jamur Entomopatogen Berformulasi Cair terhadap Plutella xylostella (L.) Di Laboratorium - Haperidah Nunilahwati; Siti Herlinda; Chandra Irsan; Yulia Pujiastuti; . Khodijah; Dewi Meidelima (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2013)
Efficacy test of liquid bio-insecticide of entomopathogenic fungi in control against Plutella xylostella in the laboratory. The insect pest P. xylostella could reduce crop production of Brassicaceae. The aim of research was to test the efficacy liquid bio insecticide with active ingredient of Beauveria bassiana and Metarhizium anisopliae fungi to control P. xylostella. Bio-insecticide was applied by spraying on mustard leaves infested with 50 individuals of third instar larvae of P. xylostella and a density of 1x106 conidia ml-1. Larval mortality was observed every 2 hours and LT50 of larvae was calculated. The study showed that the highest percentage of mortality found in Mt ES and Mt ES (cf) isolates was 99.6%, the lowest mortality at Mt NES isolate was 96.80%. LT50 and LT95 values Bb ES were the lowest i.e. 2.04 days and 2.95 days. The highest LT50 and LT95 of Mt NES isolate were 2.24 days and 3.32 days. The liquid bio-insecticide of entomopathogenic fungus B. bassiana and M. anisopliae were effective to control the larvae of P. xylostella.